Polarized backlight based on selective total internal reflection at microgrooves - Chien, KW; Shieh, HPD; Cornelissen, H (My University, 2004)
A polarized backlight for LCD illumination is designed and fabricated in which s-polarized light is extracted owing to selective total internal reflection at microstructures in the anisotropic layer. From the measurement, the contrast ratio in normal viewing direction can be as high as 64. Luminous uniformity of higher than 80% is achieved for polarized backlights. Furthermore, 1.6 gain in efficiency is obtained aiming for high-efficiency LCD illumination. (C) 2004 Optical Society of America.